The manners of Downton Abbey [videorecording (DVD)] ([Publisher not identified], 2015)
What goes on behind-the-scenes to get the manners of 1900s Britain exactly right on Downton Abbey? Discover the secrets of how the aristocratic set dined and dressed, how they married and made money, how they interacted with the servants, and above all why they behaved as they did. Includes revealing interviews with leading cast members.